Efektivitas Peningkatan Vo2max Atlet Muay Thai Dengan Metode Clicnh Work dan Skipping Rope - Selvi Nur Rianni; Iman Imanudin; Muhammad Zulfikar Romdona (Universitas Galuh, 2025)
Muay thai is a martial arts sport that requires stable physical strength and technique during the match with the aim of attacking and defending against opponent attacks. The purpose of this study was to determine the effectiveness of increasing vo2max from skipping rope training and clicnh work. The method used in this research is quantitative with experimental research type and pretest posttest research design. The samples used in this study were 4 muay thai athletes from bekasi city. This research instrument uses the bleep test to see the athlete's initial and final vo2max scores. This research data analysis technique uses the help of SPSS software version 29.0.1.0. using the data normality test and the Paired Sample T-tests test. The results showed that there was an effect of skipping rope of 0.049 <0.05 which means there is a significant increase while for clicnh work has a two-sided p value of 0.010 <0.05 which means there is an increase in vo2max in the exercise. The conclusion of these two exercises has the same increase in vo2max, but the results of data processing for significant results are skipping rope exercises because the value of data processing results is greater than clinch work exercises.